Drivers’ Growth of Islamic Banking Industry: Lesson from Malaysia - Elryah, Yagoub (International Journal of Social Sciences and Management, 2014)
Numerous studies focus on the Islamic banking performance, banks’ growth. There are, however, very little is known about the drivers’ growth of Islamic banking. The paper attempted to fill this gap. To achieve the objectives of the study, we consider government financial strategies for Islamic banking in Malaysia (Master Plan financial services 2000-2010 and Blueprint financial sector plan 2011-2020) and interviews the policy makers and regulators from BNM and selected banks. In this context, we explored the drivers’ growth Islamic banking industry in Malaysia for the period 2002-2012. The findings of the study revealed that the government strategies, high skilled banker’s human resources, financial stability, foreign banks, innovative products, awareness of the customers and quality of the financial and regulatory reforms were main drivers’ growth of Islamic banking in Malaysia. DOI: http://dx.doi.org/10.3126/ijssm.v1i4.10626 Int. J. Soc. Sci. Manage. Vol-1, issue-4: 122-128